Konsep pertanaman lanskap berdasarkan karakteristik pertamanan Bali pada lanskap New Kuta Golf - Sukmawijaya, I Wayan Gede Ari; Astiningsih, Anak Agung Made; Kohdrata, Naniek (Jurnal Arsitektur Lansekap; Vol.5, No.1, April 2019, 2019)
Concept of Landscape Cropping Based on Balinese Gardening Characteristics in New Kuta Golf Landscape. The golf course consists of two areas: the game zone and the non-game zone (out of boundary) which are generally designed with beautiful landscapes as an attraction for golfers. Landscape of New Kuta Golf that located in Bali should represent the local wisdom of Balinese landscaping. Concept of landscape cropping based on Balinese gardening characteristics in New Kuta Golf landscape was raised as a research topic to identify landscape conditions and create a golf course design concept with Balinese garden characteristics. The research was used survey method with observation technique and literature study. Stages of this research was a reference in the design which includes the stage of inventory, analysis and synthesis, and conceptualization. The results showed that landscape conditions found on the golf course New Kuta Golf was applied concept to the concept of Catur Desa. Catur Desa produces four plant zones that is Wisnu Zone, Iswara Zone, Brahma Zone, and Mahadewa Zone. This concept is uses the point of compass to determine the colors of plants applied. The results of this study were expected to uplift and preserve the cultural heritage and philosophy of Balinese landscaping.